2014
DOI: 10.1074/jbc.m114.569459
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1(+) B Cells Show Immune Suppressor Properties

Abstract: Background:The properties of regulatory B cells are not fully understood. Results: CX3CR1ϩ B cells do not express but contain ␣v␤6 and TGF-␤ and inhibit T cell proliferation. Conclusion: CX3CR1ϩ B cells have immune suppressor properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…It has been reported that CX 3 CR1 + B cells are increased in people with food allergies ( 16 ). CX 3 CR1 + B cells have transforming growth factor (TGF)-β and integrin αvβ6 that can suppress CD4 + T cell activity.…”
Section: Bone Marrow and Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that CX 3 CR1 + B cells are increased in people with food allergies ( 16 ). CX 3 CR1 + B cells have transforming growth factor (TGF)-β and integrin αvβ6 that can suppress CD4 + T cell activity.…”
Section: Bone Marrow and Immune Systemmentioning
confidence: 99%
“…CX 3 CR1 + B cells have transforming growth factor (TGF)-β and integrin αvβ6 that can suppress CD4 + T cell activity. Neonatal regulatory B lymphocytes (nBreg cells) can react with protein F of respiratory syncytial virus to upregulate CX 3 CR1 which can then react with glycoprotein G, resulting in viral infection ( 16 ). These interactions could make nBreg cells induce IL-10 production, resulting in weakened cytokine production of Th1 cells ( 17 ).…”
Section: Bone Marrow and Immune Systemmentioning
confidence: 99%
“…Enfin, il a été montré dans plusieurs études que les cellules B CX3CR1 + régulatrices étaient impliquées dans l'établissement de la tolérance orale. En effet, chez des patients souffrant d'allergie alimentaire on retrouve un taux fortement diminué de cellules B CX3CR1 positives dans le sang [60]. De plus, le transfert adoptif de cellules B régulatrices CD5 + CD19 + CX3CR1 + permet de supprimer l'allergie alimentaire dans un modèle murin [61].…”
Section: Les Récepteurs De Chimiokines Dans L'allergie Alimentaireunclassified
“…B cells (BC) are a major fraction of the immune cells in the body. Apart from producing antibodies, B cells also have an immune regulatory function via producing immune regulatory cytokines, such as interleukin (IL)-10 [ 1 ] or transforming growth factor (TGF)-β [ 2 , 3 ]. IL-10 can be produced by several cell types, including dendritic cells, T cells, BCs and monocytes, etc [ 4 ].…”
Section: Introductionmentioning
confidence: 99%